The Multiple Sclerosis (MS) Genetic Risk Factors Indicate both Acquired and Innate Immune Cell Subsets Contribute to MS Pathogenesis and Identify Novel Therapeutic Opportunities - Parnell, Grant P.; Booth, David R. (Frontiers in Immunology, 2017)
Multiple Sclerosis (MS) is known to be a partially heritable autoimmune disease. The risk of developing MS increases from typically 1 in 1000 in the normal population to 1 in 4 or so for identical twins where one twin is affected. Much of this heritability is now explained, and is due almost entirely to genes affecting the immune response. The largest and first identified genetic risk factor is an allele from the MHC Class II HLA-DRB1 gene, HLA-DRB1*1501, which increases risk about three-fold. The HLA-DRB1 gene is expressed in antigen presenting cells, and its protein functions in presenting particular types of antigen to CD4 T cells. This discovery supported the development of the first successful immunomodulatory therapies: glatiramer acetate which mimics the antigen presentation process, and interferon beta which targets CD4 T cell activation. Over 200 genetic risk variants, all single nucleotide polymorphisms (SNPs), have now been described. The SNPs are located within, or close to, genes expressed predominantly in acquired and innate immune cell subsets, indicating both contribute to MS pathogenesis. The risk alleles indicate variation in the regulation of gene expression, rather than protein variation, underpins genetic susceptibility. In this review we discuss how the expression and function of the risk genes, as well as the effect on these of the risk SNPs, indicate specific acquired immune cell processes that are the target of current successful therapies, and also point to novel therapeutic approaches. □